Structural Characterization and Remarkable Axial Ligand Effect on the Nucleophilic Reactivity of a Nonheme Manganese(III)-Peroxo Complex - Annaraj, Jamespandi; Cho, Jaeheung; Lee, Yong-Min; Kim, Sung Yeon; Latifi, Reza; de Visser, Sam P; Nam, Wonwoo (Angewandte Chemie International Edition, 2009)
The dark side of the Mn: A manganese(III) complex bearing a 13-membered macrocyclic ligand (1, see picture) binds a peroxo ligand in a side-on η² fashion. The reactivity of 1 is influenced by the introduction of anionic ligands trans to the peroxo group. Electronic and structural changes upon trans-ligand binding explain the increased nucleophilicity of the resulting complexes 1-X.